Wartości i przekonania. Ile etyki jest w etykach stosowanych? - Rotengruber, Przemysław (Humaniora. Czasopismo Internetowe, 2024)
The measure of the usefulness and credibility of applied ethics is its ability to counteract conflicts dividing social and professional groups. To achieve this goal, representatives of applied ethics must meet a basic condition by providing an epistemological justification of the claim to the validity of the judgments they formulate. Yet it is here that they encounter obstacles recognized (earlier) by ethical philosophers and sociologists of knowledge. The problem is not only the variety of moral challenges that an individual faces, but also the way in which their moral attitude is influenced by the group to which they belong. This article attempts to resolve both of these difficulties in a way that is consistent with the goals of applied ethics.